Hegemony and discourse : new perspectives on international relations - Adem, Seifudein (Lanham, Md. : University Press of America, 2005)
"Hegemony and Discourse examines contemporary theories and practices of international relations from a non-Western perspective and suggests some tentative and intriguing conclusions about the complex relationship between discourse and hegemony. The discussions revolve around two major themes. The first relates to the burning global issues in what the author calls the post post-Cold War period. These are issues arising from recent development that are having wider consequences on an international scale."--BOOK JACKET.
Foreword / Ali A. Mazrui -- 1. Ibn-Khaldun and modern historiography -- 2. Social theory and public policy -- 3. The social construction of the clash of civilizations -- 4. IR theories after the post-cold war -- 5. Ali A. Mazrui as a postmodern Ibn Khaldun.
Keywords: Hegemony